On the left side of the equation, you have like terms : 2x and 4x

That means that you can combine them

2x+4x=3x+1

6x=3x+1

Now, since the 3x is on the other side of the equation, you have to perform the opposite operation by subtracting 3x on both sides of the equation:

The 3x's will cross out on the right side of the equation

3x-3x=0x=0

On the left side:

6x-3x=3x

SO, now the equation looks like:

3x=1

Now, to get x by itself, perform the opposite operation by dividing 3 on both sides of the equation:

The 3's will cross out on the left:

3x ÷ 3 = 1x = x

On the right:

1 ÷ 3 = 1/3

x=1/3

Third angle = 180 - (44 + 72) = 180 - 116 = 64 degrees answer

5t + (t - 3) - [(7t + 5) - (8 - 3t)] (multiply -1 to (8 - 3t)

5t + (t - 3) - [(7t + 5) - 8 + 3t]

5t + (t - 3) - [7t + 3t + 5 - 8]

5t + (t - 3) - [10t - 3] (multiply -1 to [10t - 3]

5t + (t - 3) - 10t + 3

5t + t - 10t - 3 + 3

**-4t **

answer

**Answer:**

e : g = 2 : 7

**Step-by-step explanation:**

e/f = 3/7

e = 3f/7

f/g = 2/3

g = 3f/2

e/g = (3f/7)/(3f/2) = 2/7

**Answer:**

**Step-by-step explanation:**

If you are solving x then do this:

-2.3-5=x-17

First combine like term.

-7.3=x-17

Then add each side of the equation by 17 (we aren't subtracting because we are trying to get rid of -17 so to get rid of it we add by 17).

-7.3 +17 = x-17+17

9.7=x